Explorative and Exploitative Learning in Teams: Unpacking the Antecedents and Consequences - Zhao, Kai; Zong, Boqiang; Zhang, Lihua (Frontiers in Psychology, 2020)
Many organizations adopt team-based structures to better survive in the highly competitive environment. To achieve this goal, teams not only need to develop new ideas to adapt to the changing situations, but also follow standardized procedures to complete tasks effectively, suggesting the importance of ambidextrous capacity on addressing the paradoxical demands. However, we have little knowledge about both of how to respectively facilitate team ambidextrous learning (i.e., team explorative and exploitative learning) and how team the two learning activities contributes to team effectiveness. Using the multi-time and multi-source data gathered from 140 teams in 6 Chinese companies, we found that team leader’s power sharing and management control behaviors (i.e., ambidextrous leader behaviors) specifically enhanced team explorative and exploitative learning. In addition, our results showed that team explorative and exploitative learning drove overall team performance via the mechanisms of team creativity and task completion respectively. The theoretical and practical implications, limitations, and future research directions are discussed as well.